Kemampuan Menulis Teks Eksposisi Siswa Kelas VIII SMP Negeri 2 Hulu Kuantan - Apridin, Apridin; Kosim, Kosim; Wisni, Firda; Wahyudi, Wahyudi; Harliana, Harliana (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aims to enhance eighth-grade students' exposition writing at SMP Negeri 2 Hulu Kuantan through a problem-based learning model. The model facilitates material understanding, improving students' expository text skills and overall proficiency. Noteworthy improvements are observed in the learning process and outcomes. Classified as Classroom Action Research, the research consists of two cycles at SMP Negeri 2 Hulu Kuantan. Data collection includes tests and observations, analyzed qualitatively. Success criteria involve positive value changes in each cycle, assessing triumph in both the process and results. The problem-based learning model effectively elevates students' exposition writing proficiency, fostering focus, group engagement, and enjoyment. Consistent and significant improvements occur across all aspects from cycle I to II, affirming the model's success in enhancing exposition writing skills among eighth-grade students at SMP Negeri 2 Hulu Kuantan.